Exploring the propensity to travel by demand responsive transport in the rural area of Lincolnshire in England. Issue 2 (June 2015) - Wang, Chao; Quddus, Mohammed; Enoch, Marcus; Ryley, Tim; Davison, Lisa
Highlights Shows how individual level factors influence the use of rural DRT systems. Applies ordered logit model to a survey of DRT users in Lincolnshire, UK. DRT used most to travel for work, by disabled and more rural residents. Emerging market potential for DRT from the retired male market segment.